Upaya Peningkatan Kompetensi Siswa JurusanAkuntansi Di Smk Muhammadiyah 2 Klaten Utara Dalam Rangka Menghasilkan Tenaga Kerja Profesional Tingkat Menengah - Astrianingsih, Fenti, Dra. Titik Asmawati, SE, M.Si (2017)
The research aims to describe: (a) efforts to improve the competence of students majoring in accounting at SMK Muhammadiyah 2 Klaten Utara, (b) the relationship between the competence of students majoring in accounting with the competence of the workforce. The type of this research is qualitative research and an ethnography desaign which is done for 3 months. The research subjects: (a) accounting teachers (b) students of class X AK I, X AK II, and X AK III at SMK Muhammadiyah 2 Klaten Utara with 94 students. Data collection methods used are data collection, data reduction, display data, and conclusions. The result of the research shows that the effort of increasing the competence of students is divided into four competencies, including: (1) Cognitive Competence, the effort is done by focusing on Teaching and Learning Activities (TLA) on teaching materials. (2) Psychomotor Competence, through accounting practice during school learning and through Industrial Work Practice in the world of work. (3) Affective Competence, through counseling activities as an individual or group approach with the help of accounting teachers or BK teachers and all parties within the scope of the school, because the increase in affective competence itself can not be separated from social interaction. (4) Akhlakul Kharimah Competence, that is with the holding of activities based on Islamic values. Efforts to increase student competence of the four competencies are supported by the role of teachers as active actors and the availability of adequate facilities.